Penyuluhan Penyusunan Akuntabilitas dan Transparansi Keuangan Pada SDN 1 Aji Jaya KNPI - Nurohmayni Putri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This community service activity aims to increase understanding and ability in preparing accountable and transparent financial reports at SDN 1 Aji Jaya KNPI. Through this outreach, it is hoped that the school can manage school operational assistance funds more effectively and efficiently and can properly account for them to interested parties. In this activity, lecturers from the Mitra Indonesia University Faculty of Business Study Program provided practical guidance and training to teachers and school staff, including direct practice in preparing financial reports based on real cases in schools. Evaluation is carried out through an assessment of financial reports prepared by participants as well as feedback from participants regarding counseling materials and methods. The results include increased understanding of teachers and school staff regarding financial accountability and transparency, the realization of accountable and transparent financial reports at SDN Aji Jaya KNPI, as well as increased trust from parents and other parties in the management of school operational assistance funds. Through this effort, it is hoped that it can increase accountability and transparency in financial management at the school, as well as optimize the use of school operational assistance funds to improve the quality of education.